Genetic diversity and its association with Phytophthora palmivora resistance in Durian (Durio zibethinus) using RAPD markers - SUDIRMAN NUMBA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Numba S. 2023. Genetic diversity and its association with Phytophthora palmivora resistance in Durian (Durio zibethinus) using RAPD markers. Biodiversitas 24: 4542-4548. Durian (Durio zibethinus L.) is a popular tropical fruit that contributes significantly to regional economic value. Root and stem rot disease caused by Phytophthora palmivora has become a serious threat to the growth and development of durian. Indonesia has various local durian varieties that have the potential of resistant to P. palmivora. This study aims to analyze genetic diversity and its association with the resistance of durian to root and stem rot disease caused by P. palmivora using RAPD markers. Ten varieties of durian were compared with those of 2 wild species, namely D. kutejensis (Hassk.) Becc. and Boschia excelsa Korth.. The DNA profile analysis was performed by using 10 RAPD primers. Furthermore, cluster analysis was done using the NTSYS (Numerical Taxonomic and Multivariate Analysis System) ver. 2.0. Observation of the DNA profile (DNA banding pattern) showed that all the primers succeeded in producing amplified DNA fragments. Of the total 78 bands produced, 10 bands were considered monomorphic, while 68 bands (87.20%) were considered polymorphic. The high level of polymorphism causes a low level of similarity between varieties so that not all resistant varieties are grouped in the same cluster. This study found that the 1kb band produced by the OPA-2 primer was a potential gen associated with resistance to P. palmivora. It is suggested to carry out further tests on crosses of resistant and susceptible varieties.